IMPROVING STUDENT LEARNING OUTCOMES IN MULTIPLE MATERIALS USING THE JARIMATICS METHOD ASSISTED OF THE MULTIPLE SMART BOARD - Robiatul Adewiyah; Evi Novita Sari; Fitri Wijayanti; Ana Naimatul Jannah (Citra Dharma Cindekia, 2022)
Learning outcomes can be used as an indicator of the success of a study. Based on the results of a preliminary study conducted by the researcher, most of the second grade students at SDN Demangan 1 Bangkalan have low learning outcomes in the subject matter of multiplication in mathematics. To overcome this, the researcher plans to take action in a study, namely using the jarimatics method assisted by multiplication smart board media with the aim of increasing student learning outcomes in multiplication material. This research is a class action research with a class action method. Data collection techniques were carried out using observation techniques, interviews, documentation, and tests. The collected data were then analyzed using quantitative data analysis techniques. The results of this study indicate that the use of the jarimatics method will improve student learning outcomes on multiplication material using multiplication smart board media. This is shown by the increase in average learning outcomes and the percentage of students who complete each cycle. In cycle I, the average learning outcomes are still below the minimum completeness criteria, namely 54.4 with a percentage of 39%. This increased in cycle II to an average of 71 with a percentage of 81 students completing